2006
DOI: 10.1111/j.1365-2672.2006.02876.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of hepatitis A virus in water samples in Thailand

Abstract: Aims:  Outbreaks of hepatitis A in Thailand have been reported continuely and associated with water supply. However, the genetic analysis of hepatitis A virus (HAV) in water is limited. This study described the application of virus concentration method and reverse transcriptase‐nested polymerase chain reaction (RT‐nested PCR) to detect HAV RNA and analyse the genetic sequence of the virus in environmental water samples. Methods and Results:  The HAV from water samples was concentrated by using a developed viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
1
24
1
1
Order By: Relevance
“…Sewage from households may have been present in the tested water samples. However, the detection rates of viral genes in our study were lower than those in reports examining other environmental water sources in Thailand (19)(20)(21). The differences in these detection rates may also be explained by differences in the targeting samples (flood water versus normal environmental water).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Sewage from households may have been present in the tested water samples. However, the detection rates of viral genes in our study were lower than those in reports examining other environmental water sources in Thailand (19)(20)(21). The differences in these detection rates may also be explained by differences in the targeting samples (flood water versus normal environmental water).…”
Section: Discussioncontrasting
confidence: 55%
“…Data from other studies conducted in Thailand showed that some enteric viruses (or their genes and/or antigens) were present in non-flood environmental water from canals, swamps, or sewage (19)(20)(21). However, to the best of our knowledge, there are no previous reports of NV or HEV in any type of environmental water in Thailand.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Also, the use of pools found in the river for recreational activities like swimming is common practice among rural children, which raises both the chances of surface water contamination with enteric viruses and also the risk of swimmers getting infected. Waterborne RVs have been detected elsewhere (Kittigul et al, 2005b) and the first large waterborne epidemic in an adult population was caused by Group B rotaviruses in China (Logan et al, 2006). Faecally-polluted natural surface water used for recreational activity could therefore pose a potential health risk to the public (Venter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%